2020
DOI: 10.1111/nph.16545
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evidence of root colonization suggests ecological versatility in the genus Mycena

Abstract: Summary The root‐associated habit has evolved on numerous occasions in different fungal lineages, suggesting a strong evolutionary pressure for saprotrophic fungi to switch to symbiotic associations with plants. Species within the ubiquitous, saprotrophic genus Mycena are frequently major components in molecular studies of root‐associated fungal communities, suggesting that an evaluation of their trophic status is warranted. Here, we report on interactions between a range of Mycena species and the plant Betu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 77 publications
9
40
0
Order By: Relevance
“…1b ). This is consistent with recent estimates (78–110 7 and mean 125 1 Mya) and overlaps with the initial rise and diversification of angiosperms 22 , suggesting that they are ecologically associated with fungi acting as saprotrophs or mycorrhizal partners 3 . Finally, the age of bioluminescence which was also the age of functional luciferase in fungi was estimated to originate around 160 million years ago during the late Jurassic ( Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1b ). This is consistent with recent estimates (78–110 7 and mean 125 1 Mya) and overlaps with the initial rise and diversification of angiosperms 22 , suggesting that they are ecologically associated with fungi acting as saprotrophs or mycorrhizal partners 3 . Finally, the age of bioluminescence which was also the age of functional luciferase in fungi was estimated to originate around 160 million years ago during the late Jurassic ( Fig.…”
Section: Resultssupporting
confidence: 90%
“…1a ), and a gilled or porioid hymenophore 2 . Mycena also have a diversity of life history strategies; while many species are saprotrophic, they can be pathogens as well as mycorrhizal 3 . Despite its vast diversity of lifestyles and phenotypes, there are many outstanding questions concerning the basic biology, ecology and genomics of this genus.…”
mentioning
confidence: 99%
“…High temperatures that are measured in the region in summer [27] and closeness to a water body (flooding or exposure to airborne water from river surface evaporation) may have favored the decomposition of SOM in June/August and, therefore, the establishment of root associations with fungi with high decomposing abilities that would increase plant N intake [110]. It has been confirmed that some saprotrophic fungi (also detected here) can indeed establish a facultative biotrophic relationship with roots [81,88,111]. On the other hand, alkaline soil environment (as detected here) has rarely been connected to ECM domination [7,112].…”
Section: Dominance Of Saprotrophs and Symbiotrophs Across The Seasonssupporting
confidence: 70%
“…and Sebacina sp., as well as endophytes like Cladophialophora sp., Humicola sp., Mycena sp., Mortierella sp.) were commonly detected in ectomycorizomes of black truffle-producing habitats [72,81]. However, Cennococum sp., Entholoma sp., Phallus sp., which were common in autumn black truffle-producing soils are assumed to be more frequent in dry or acidic soils [13,72].…”
Section: Root-associated Fungal Communities In Balkan Riparian Forestmentioning
confidence: 99%
See 1 more Smart Citation